Financial Performance Comparison of Islamic and Conventional Banking in Selected Countries using the CAMEL Model - Rahim Dabbagh; Hasan Golmoradi; Arash Bagri (مطالعات مالی و بانکداری اسلامی, 2019)
In this research, the effect of banking factors on the financial performance of Islamic and conventional banking has been studied. In Comparison of Islamic and conventional banking, the effect of banking factors such as capital adequacy, asset quality, bank size, management quality, and profitability in the form of CAMEL Model have been investigated and their impact on each of the banking methods has been measured for 10 banks in 5 selected countries. Their profitability has been evaluated based on three models with dependent variables such as asset return rate, return on equity and profit margin and for bank stakeholders; the profitability of the banking system is determined by financial performance. From the analysis of regression models (panel data during 2010-2017), it is determined that Islamic banking in all three models is superior to the conventional banking in bank size indices and cost to income ratio. Also, conventional banking in the model with the rate of return on assets, capital adequacy ratios, loans to deposits and deferred loans to total loans as dependent variables is superior to Islamic banking. It is suggested that Islamic banks in loan payment consider accurate validation of applicants and more detailed justification plans; and develop and promote the Islamic Banking Indicators by launching the Risk Management Committee.